Characteristics of Lignin from Solid Waste Empty Palm Fruit Bunches (EPFB) using the Organosolv Method - Pramana, Angga; Zalfiatri, Yelmira; Irawan, Wawan; Rovarti Ningsih, Arum; Gunawan, Chandra; Putri, Vivin Jenika; Rahmah, Anania (Jurnal Bio-Geo Material Dan Energi, 2026)
Oil palm empty fruit bunches are solid waste from the palm oil processing process that contains a significant amount of lignin and cellulose. Oil palm empty fruit bunches are widely found in Indonesia, especially in Riau Province. The processing of oil palm empty fruit bunches has not been effectively utilized. Therefore, the author isolated cellulose from oil palm empty fruit bunches using the organosolv method. The organosolv method is a type of isolation method that is environmentally safe than the kraft process, as it employs solvents in the form of organic chemicals, such as formic acid and acetic acid. This research was conducted by varying the ratio of the solvent solution using acetic acid and formic acid. Various solutions were employed, namely P1=20 ml formic acid+140 ml acetic acid, P2=40 ml formic acid+120 ml acetic acid, P3=60 ml formic acid+100 ml acetic acid, P4 = 80 ml formic acid+80 ml acetic acid, P5=160 ml formic acid, and P6=160 ml acetic acid. The best results were obtained in the P2 treatment with a variation of 40 ml formic acid + 120 ml acetic acid and obtained a high level of yield, namely in the P2 treatment it was 56.85%, the water content was 4.70%, the ash content was 4.84%, the acidity level (pH) was 4.67 and FTIR test results show wave peaks in treatments P3 and P6 28 waves